2020
DOI: 10.1136/neurintsurg-2020-016966
|View full text |Cite
|
Sign up to set email alerts
|

Per-pass analysis of acute ischemic stroke clots: impact of stroke etiology on extracted clot area and histological composition

Abstract: BackgroundInitial studies investigating correlations between stroke etiology and clot composition are conflicting and do not account for clot size as determined by area. Radiological studies have shown that cardioembolic strokes are associated with shorter clot lengths and lower clot burden than non-cardioembolic clots.ObjectiveTo report the relationship between stroke etiology, extracted clot area, and histological composition at each procedural pass.MethodsAs part of the multi-institutional RESTORE Registry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 30 publications
5
51
0
Order By: Relevance
“…Given the increased utilization of mechanical thrombectomy for the treatment of acute ischemic stroke secondary to large vessel occlusion, there has been growing interest in the analysis of retrieved thrombi 1–7. A number of studies have suggested that histopathological analysis can provide some valuable insights into stroke etiology 8–11.…”
Section: Introductionmentioning
confidence: 99%
“…Given the increased utilization of mechanical thrombectomy for the treatment of acute ischemic stroke secondary to large vessel occlusion, there has been growing interest in the analysis of retrieved thrombi 1–7. A number of studies have suggested that histopathological analysis can provide some valuable insights into stroke etiology 8–11.…”
Section: Introductionmentioning
confidence: 99%
“…Other recent work in our lab has found that clot composition varies with stroke aetiology (Fig. 3) (Fitzgerald et al, 2020). There are still many unanswered questions, and much left to learn.…”
Section: Stentrieversmentioning
confidence: 83%
“…However, our findings also show that smaller clots were not associated with better recanalization outcome or lower number of passes, which could be related to clot properties and composition, since it has been demonstrated that small, difficult to remove clots are more platelet rich and contain more highly organised fibrin regions. 19,20 It has been demonstrated that administration of rtPA before mechanical thrombectomy reduces clot size. 21 The present study demonstrates the correlation between clot length on CTA/NCCT and area of extracted clot was slightly stronger for the cohort of patients that directly underwent mechanical thrombectomy compared to the patients pre-treated with rtPA.…”
Section: Discussionmentioning
confidence: 99%